KORELASI TINGKAT PERTUMBUHAN EKONOMI DAN KETIMPANGAN PENDAPATAN DI PROVINSI JAWA TIMUR PERIODE 2015–2024 - Ainun Defrilia; Ngafifudin Asrofi; Sabila Hidayatussolikah; Ines Kiki Faradila Hardika Dini; Agus Eko Sujianto (Politeknik Negeri Lhokseumawe, 2026)
This research seeks to examine the connections between how the economy advances and how income is spread unevenly across East Java Province from 2015 to 2024. The information utilized was obtained from official publications by the Statistics Indonesia and scrutinized using quantitative methods, incorporating correlation tests and regression to reveal the effects of economic expansion on the degree of income inequality. The research findings indicate that a rise in Gross Regional Domestic Product does not automatically translate to decreased disparity, some regions experiencing rapid economic growth still face substantial income inequality. Essential components such as dissimilarities in job prospects, discrepancies in minimum wages, and the clustering of economic actions are crucial elements that play a part in the uneven distribution. These outcomes highlight the necessity of creating more encompassing policies to ensure that the benefits of economic advancement are fairly shared by all societal segments in East Java. Keywords: Correlation Analysis, Economic Disparity, East Java GRDP, Economic Growth, Income Inequality, Inclusive Growth.